Dental health practices versus oral health condition in 12-year-old children from West Pomerania Province - Rojek, Rafał; Stachowiak-Ruda, Joanna; Mikołajczyk, Joanna; Wieczkowska, Ilona; Jarząbek, Anna; Gońda-Domin, Magdalena; Węsierska, Karolina (Journal of Stomatology, 2017)
Introduction. Oral health condition is a result of numerous factors, and hygiene-nutrition practices play a key role in this respect. Aim of the study. To assess the condition of health in 12-year-old children from West Pomerania Province in the light of their awareness of caries prevention and health-oriented practices. Material and method. The study covered a group of 120 children – 12 years of age – living in the area of Łobez (a small town). The clinical examination was performed to assess the condition of the teeth by means of caries prevalence and frequency index. The condition of the teeth was assessed according to the WHO criteria by duly qualified dental practitioners. The questionnaire survey provided the data on oral health conditions and eating habits of the children concerned. Results. The prevalence of caries in the entire group of children from the small town and rural areas was 86.7%. Almost 60% of the children required dental treatment and it concerned significantly more children from the rural areas compared to those living in the town. Nearly 2/3 of country children needed treatment of caries significantly more frequently compared to their town peers. In our study, the DMFT score in the children from the small town was 2.73 while the children from the rural areas exhibited the DMFT score of 4.35. The caries treatment index in the entire group of 12-year-old children was low and was found to be 0.38. The most common reason (62% of cases) to present at a dental office was a need to restore a